Reassessment of the taxonomic status of pseudopaludicola parnaiba (Anura, leptodactylidae, leiuperinae), with the description of a new cryptic species from the Brazilian cerrado - de ANDRADE, Felipe Silva; Haga, Isabelle Aquemi; Lyra, Mariana Lúcio [UNESP]; de CARVALHO, Thiago Ribeiro [UNESP]; Haddad, Célio Fernando Baptista [UNESP]; Giaretta, Ariovaldo Antonio; Toledo, Luís Felipe (Museum National D'Histoire Naturelle, 2020)
The Neotropical frog genus Pseudopaludicola includes 25 species distributed throughout South America. Herein we review the taxonomic status of P. parnaiba relative to P. canga and the specific identity of the population treated in previous studies as Pseudopaludicola sp. 3 from Barreirinhas in the Brazilian state of Maranhão. The lack of differentiation in advertisement call, morphology, and mitochondrial markers from topotypes and different populations rejects the status of P. parnaiba and Pseudopaludicola sp. 3 from Barreirinhas as distinct species. For these reasons, we suggest to formally consider P. parnaiba as a junior synonym of P. canga. We also found that a population previously reported as P. facureae from central Brazil (Palmeiras de Goiás, Goiás) corresponds to a cryptic species that we describe here as a new species. Lastly, we provide for the first time the phylogenetic positions of P. giarettai, P. llanera and P. pusilla.
Keywords: Integrative taxonomy; Mitochondrial DNA; Morphologically cryptic species; Pseudopaludicola canga